Modeling techniques in counseling in high school to improve the behavior prosocial - Sari, Nina Permata; Setiawan, Muhammad Andri; Andriani, Rosida (Indonesian Institute for Counseling, Education and Therapy (IICET), 2020)
The development of the technological era 4.0 which has an impact on the erosion of individual awareness of the social environment is characterized by low prosocial behavior. Alternative solutions offered to improve prosocial behavior through the use of modeling techniques, by using this technique the goal achieved is to improve the ability of prosocial behavior in high school students. This study took place in SMAN 9 Banjarmasin, based on the distribution of questionnaires obtained by 6 students who have low prosocial behavior. Based on the results of the investigation statistically, the results show the value of z = -2.201 while for the value of ztab = -0.0139, which means zhit>ztab so that Ha is accepted and at the Asymp value. Sig. (2-tailed) = 0.028